Mapping of fuels and fire potentials in the African Continent using FCCS - M.L. Pettinari; E. Chuvieco (Revista de Teledetección)
This paper presents the methodology used for the development of a fuel map for the African Continent, using FCCS (Fuel Characteristic Classification System). The cartography of the fuelbeds was based on global cartographic information obtained from remote sensing imaging, and the variables associated to each fuelbed were extracted from existing vegetation databases. A total of 75 fuelbeds were developed, and from the variables assigned to each of them, different Fire Potentials were calculated using default environmental variables. These potentials allow the estimation of surface fire behavior, crown fire and available fuel, depending on the characteristics of the existing vegetation.